2000
DOI: 10.1051/aas:2000282
|View full text |Cite
|
Sign up to set email alerts
|

CCD photometry, spin and shape models of five asteroids: 225, 360, 416, 516, and 1223

Abstract: Abstract. New CCD photometric observations for 225 Henrietta (1995), 360 Carlova (1996, 1997, 1998), 416 Vaticana (1995-96, 1998), 516 Amherstia (1995, 1996, and 1223 Neckar (1995-96) carried out at five observatories are presented. New synodical periods for two asteroids (225, 1223) have been obtained. Using all available lightcurves, the spin vectors, senses of rotation, and triaxial elipsoid models of these five asteroids have been determined or refined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…Observations of other asteroids performed in Borowiec have been already published, together with the new models in, for example, Michałowski et al (2000Michałowski et al ( , 2001, Kryszczyńska et al (2003), Ďurech et al (2007), and in the three previous papers of the present series - Michałowski et al (2004Michałowski et al ( , 2005Michałowski et al ( , 2006.…”
Section: Observations Of Three Main Belt Asteroidsmentioning
confidence: 78%
“…Observations of other asteroids performed in Borowiec have been already published, together with the new models in, for example, Michałowski et al (2000Michałowski et al ( , 2001, Kryszczyńska et al (2003), Ďurech et al (2007), and in the three previous papers of the present series - Michałowski et al (2004Michałowski et al ( , 2005Michałowski et al ( , 2006.…”
Section: Observations Of Three Main Belt Asteroidsmentioning
confidence: 78%
“…We carried out optical photometric observations of 1998 SF36 during its 2001 apparition, using the 105-cm Kiso Schmidt telescope with the SITe 2KCCD, the 50-cm NAOMitaka telescope with the Astromed CCD (Dermawan et al, 2002) and the 105-cm Pic du Midi telescope with the Thomson CCD (Michałowski et al, 2000). The observational conditions are summarized in Table 1.…”
Section: Observations and Data Reductionmentioning
confidence: 99%
“…The published data come from Harris & Young (1983), Di Martino et al (1987), Dotto et al (1995), and Michalowski et al (2000). The time stamps of all involved observations were corrected by the light time and then converted into JD in the TDB time system.…”
Section: Observations and Data Reductionmentioning
confidence: 99%
“…Until now, no other direct evidence confirms the binarity of (171) Ophelia except the V-shape minima of the light curves and, in addition, no pole orientation and shape information have been derived for it. Several groups studied the spin parameters and shape of (360) Carlova (Harris & Young 1983;Di Martino et al 1987;Michalowski et al 2000;Ďurech et al 2009;Wang & Zhang 2006), and reported inconsistent spin parameters because different data sets or different analysis methods were used. The last analysis for Carlova was made byĎurech et al (2009) with the convex inversion technique using six published light curves at two apparitions, from which a pair of poles slightly different from those previously published were given.…”
Section: Introductionmentioning
confidence: 99%